Modelling the sustainable agriculture management adaptation practices: Using adaptive capacity as a mediator - Masud, Muhammad Mehedi; Akhtar, Rulia; Al Mamun, Abdullah; Uddin, Md. Sayed; Siyu, Long; Yang, Qing (Frontiers in Environmental Science, 2022)
The purpose of this research is to investigate adaptation the mediating role of farmers' adaptive capacity between behaviour and economic, social, natural, technological, and institutional limitations. A survey questionnaire was employed to collect the data, and subsequently analysed using Structural Equation Modelling (SEM). The entire population were clustered into 27 Pertubuhan Peladang Kawasan (PPK), out of which 384 targeted respondents were randomly selected from six clusters for data collection. The findings revealed that only 67% farmers are aware of adaptation practices, while 33% are uninformed. The study also revealed that economic, social, natural, technological, and institutional barriers weaken farmers’ adaptive capacity level and ultimately hamper their adaptation practices. This result further affirms the influence of farmers’ adaptive capacity level on their adaptation behaviour. To mitigate the negative effects of climate change, adaptation strategies are essentials. However, the success of these strategies is contingent upon the farmers’ adaptive capacity level, which is strained by several barriers. The findings contribute to the development of a national adaptation plan in a bid to aid the implementation of 2011-2020 National Agri-Food Policy (NAP) to increase the competitiveness and production capacity of the entire agri-food industry value chain and ensure food security in Malaysia. This study will guide policymakers in formulating an appropriate policy framework to eradicate associated obstacles, which impede adaptation capacity and practices.